Flavonoid profiling of a traditional Chinese medicine formula of Huangqin Tang using high performance liquid chromatography - Tao Li; Shuaixing Zhuang; Yiwei Wang; Yanli Wang; Weihao Wang; Huihui Zhang; Li Chen; Dunfang Wang; Zhongming Zhou; Weipeng Yang (Elsevier, 2016)
The quality control processes for herbal medicines have been problematic. Flavonoids are the major active components of Huangqin Tang (HQT, a traditional Chinese medicine formula). In this study, we used a combinative method approach consisting of chromatographic fingerprinting (high performance liquid chromatography; HPLC), quantitative methods and a pharmacodynamic evaluation model to analyze the flavonoids of HQT obtained from different sources. Ten batches of HQT were analyzed by the HPLC fingerprinting method and 26 common peaks were detected, of which 23 peaks corresponded with the chemical profile of HQT. In addition, 11 major compounds were identified by LC-MS analysis (liquid chromatography-tandem mass spectrometer; LC-MSn) and quantified by the HPLC quantitative method approach. The studied 10 batches of HQT were found to be homogeneous in their composition with a similarity between 0.990 and 1.000. The distribution of the 11 identified compounds was found to be very similar among the batches. Only slight pharmacodynamic differences were detected between the different batches, confirming the homogeneity of HQT. The results of this study prove that the combination of chromatographic fingerprinting and quantitative analysis can be readily used for comprehensive quality control of herbal medicines.